Impact of Clostridium difficile Infection on Patients' Quality of Life: a French Hospital Prospective Study. (4th October 2017) - Barbut, Frederic; Galperine, Tatiana; Vanhems, Philippe; Le Monnier, Alban; Jeanbat, Viviane; Duburcq, Anne; Alami, Sarah; Bensoussan, Caroline; Fagnani, Francis
Abstract: Background: Few data are available on the impact of episodes of Clostridium difficile infection (CDI) on quality of life. The Cdiff32, a new specific health-related quality of life questionnaire recently validated, allows such a measurement (Garey et al. J Clin Gastroenterol 2016 Sep;50(8):631–7). Methods: An observational prospective study was performed in 7 French acute-care facilities in 2016. All consecutive patients presenting with a bacteriologically-confirmed CDI during a hospital stay, regardless of reason for hospitalization, were enrolled. Two instruments were presented to patients at 7(±2) days after CDI diagnosis: the Cdiff32 and a generic questionnaire the EQ-5D-3L. The Cdiff32 comprises 32 self-administered questions about the impact of CDI in 3 broad domains (physical, mental and social). The physical domain differentiates general (6 questions) and specific physical complaints (8 questions). The mental domain comprises 14 questions about current and future anxiety. Four questions cover the impact on social relationships. Each item is scored from 0 (worst score) to 100 (best score) and they are aggregated by domain and globally. Clinical variables were collected to characterize the infection severity (ZAR score) and comorbidities. A regression analysis of the Cdiff32 scores with the EQ-5D-3L was performed. Results: 80 patients were enrolled and 3 were excluded because of missing data. The median age was 71 years and 45% were males. The global Cdiff32 score was 50.4 (SD: 17.1) with a large variability among patients (min 18.3, max 90.2). The highest impact of CDI was observed on the general physical complaints (41.6), as well as the level of current anxiety (41.6). The score relating to the social relationships was the highest (63.7). The severity of CDI (as defined by the Zar score) and the global Cdiff32 score were correlated essentially through the physical sub-score ( P = 0.0154). Patients with recurrences had a lower mental score compared with patients with an initial episode ( P = 0.0582). The regression analysis of global Cdiff32 score and EQ-5D-3L utility score showed a positive relationship (R 2 =0.317). Conclusion: The Cdiff32 allowed to estimate the important impact on quality of life of CDI especially on the physical domain. Disclosures: All authors: No reported disclosures.